1999
DOI: 10.1046/j.1365-2346.1999.00427.x
|View full text |Cite
|
Sign up to set email alerts
|

Responders and non-responders to post-operative pain treatment: the loading dose predicts analgesic needs

Abstract: The study compares responders and non-responders to post-operative patient-controlled analgesia (PCA) and evaluates factors that might differ between these two groups in order to identify non-responders during the early post-operative period. A prospective, randomized, double-blinded study design was used. Patients recovering from abdominal surgery were assigned to one of three treatment groups for a study period of 48 h. After titration of an individual loading dose, patients could self-administer 1 mL bolus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
0
5
0
2
Order By: Relevance
“…We know that the size of loading dose of morphine and the use of the pain scores during the first 30 minutes of post operative care are useful in assessing the pattern of response in managing the pain. 23 This supports an early and aggressive bolus dose adjustment strategy for PCA use. We assume that mobilization was associated with most of the ineffectual doses and pain during mobilization is complex.…”
Section: Discussionmentioning
confidence: 58%
“…We know that the size of loading dose of morphine and the use of the pain scores during the first 30 minutes of post operative care are useful in assessing the pattern of response in managing the pain. 23 This supports an early and aggressive bolus dose adjustment strategy for PCA use. We assume that mobilization was associated with most of the ineffectual doses and pain during mobilization is complex.…”
Section: Discussionmentioning
confidence: 58%
“…These patients represent 25% to 40% of the population and have been previously described as "nonresponders." [20,21] Stamer et al [20] were the first to identify a subgroup of nonresponders who had higher pain scores and required more analgesic consumption than their "normal" counterparts. Bar Meir et al [18] found a distinct non responder subgroup of patients who had elevated pain scores despite higher morphine consumption after flap DIEP reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The unpredictability of opioid effectiveness can be another limitation to opioid therapy, in that there is considerable variation in treatment response among patients. In a study of patient-controlled morphine for postsurgical pain, 40.4% of patients were classified as "non-responders" to morphine [49]. Thus, clinicians prescribing morphine to chronic pain patients for longterm use must be prepared to work closely with the patient to find the correct opioid and titrate the optimal dose.…”
Section: Limitations Of Opioid Therapy For Chronic Non-cancer Painmentioning
confidence: 99%